Pair-wise cointegration in long-run growth models - Stefan Bergheim (Deutsche Bank Research, 2007)
This paper presents a novel theoretical and empirical approach to the analysis of long-run economic growth. It shows that most traditional theoretical models share the feature of pair-wise cointegration among the main variables. An augmented Kaldor model is proposed in contrast to the standard production function. The empirical analysis employs non- stationary panel techniques on two groups of countries to show that pair- wise cointegration exists among GDP, physical capital, human capital, and trade openness.
Keywords: 330; Wachstumstheorie; Kointegration; Wirtschaftswachstum; Schätzung; Theorie; Welt